AB0864 The impact of disease activity, structural damage, and fatigue on physical function in patients with ankylosing spondylitis: differences in early and late disease. (12th June 2018) - He, J.; Sari, I.; Inman, R.; Haroon, N.
Abstract : Background: In patients with ankylosing spondylitis (AS), the physical function impairment caused by the disease is among the biggest concerns for both patients and clinicians. Previous studies have shown that disease activity and structural damage are the main underlying causes for physical function impairment. There is accumulating evidence that suggests fatigue as well contributes to functional limitations. However, the differential impact of these factors on physical function at early and late stage of disease remains unclear. Objectives: Study the strength of association in AS patients with varying disease duration, between physical function and the three potential determinants of interest: disease activity, structural damage, and fatigue. Methods: AS patients satisfying the modified New York criteria were followed from 2003 to 2017. Patients completed a standardised annual protocol including demographic and clinical factors, with radiographic data collected biennially. Baseline physical function (BASFI) was analysed for association with factors including disease activity (BASDAI), radiographic changes (mSASSS), and fatigue (FSS). The same analysis was conducted again with patients sub grouped with respect to disease duration (<5 years, 5–9 years, 10–20 years, >20 years), and again with respect to change in BASFI between the first and last patient visit. Multivariable regression analysis was performed to identify independent predictors of physical function at baseline and the change with time. Results: A total of 611 patients were followed and completed the standard protocol (mean age at initial visit 38.2 years; 74% male; 76.5% HLA-B27+). At baseline BASFI was independently associated (table 1) with BASDAI (p<0.0001), CRP (p<0.0001), mSASSS (p<0.0001), and FSS (p<0.0001). In the disease duration subgroup analysis, BASFI was independently associated with BASDAI (p<0.05) and mSASSS (p<0.05) in all disease durations, and with FSS in subgroups with disease duration of 5 years or greater (p<0.05). In the longitudinal analysis, change in BASFI was independently associated with changes in BASDAI (p<0.0001) and FSS (p<0.05), but not with change in mSASSS (p=0.283). Conclusions: The study demonstrated that disease activity and structural changes consistently contributes to physical function impairment in both early and late stages of disease. Fatigue does not associate with physical function at early stages of the disease, but it increases in contribution to functional impairment as disease duration increases. Disclosure of Interest: None declared